1990
DOI: 10.1007/bf01804382
|View full text |Cite
|
Sign up to set email alerts
|

Complementation studies in human and caprine β‐mannosidosis

Abstract: Cell fusions were performed to investigate the possible involvement of different gene mutations in five patients with isolated beta-mannosidosis and a patient with a combined deficiency of beta-mannosidase and heparin sulphate sulphamidase. In none of the combinations of cell lines was beta-mannosidase activity restored in the fused cell culture. Similarly, no complementation of sulphamidase activity was observed after fusion of cells with the combined deficiency and cells with isolated sulphamidase deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Complementation studies in fused cell cultures made by Hu et al (1991) (fibroblast strains from five patients with P-mannosidase deficiency and the patient with combined P-mannosidosis and sulphamidase deficiency) do not show restoration of any enzyme activity. This result rules out the presence of possible inhibitors and suggests that human P-mannosidosis is caused by allelic mutations, probably in the structural P-mannosidase gene.…”
Section: Discussionmentioning
confidence: 94%
“…Complementation studies in fused cell cultures made by Hu et al (1991) (fibroblast strains from five patients with P-mannosidase deficiency and the patient with combined P-mannosidosis and sulphamidase deficiency) do not show restoration of any enzyme activity. This result rules out the presence of possible inhibitors and suggests that human P-mannosidosis is caused by allelic mutations, probably in the structural P-mannosidase gene.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have suggested that human and caprine β-mannosidosis are both most likely caused by allelic mutations in the structural β-mannosidase genes. 14 Recent studies on mutation analysis have identified the gene localized to chromosome 4q22–25, 15 and the gene consisting of 17 exons. 16 Prenatal diagnosis is possible in this condition since β-mannosidase activity is highly expressed in chorionic villi and amniotic cells.…”
Section: Discussionmentioning
confidence: 99%